Stoichiometry Determination Across the Face of Hg1-xCdxTe Semiconductors - Banisaeid, S.; Rahemi, H.; Tayyari, S.F. (Asian Journal of Chemistry, 2016)
Variation of E1 and E1 + D1 band gap energies of mercury cadmium telluride with composition x across the face of a number of p-type and n-type samples have been determined. A three-dimensional presentation of these variations has been introduced.